PENGARUH INTERVENSI PENAMBAHAN FITOSTEROL PADA MINYAK GORENG SAWIT TERHADAP PROFIL LIPID SUBJEK DENGAN SINDROMA METABOLIK - Nurdin, Naufal Muharam; Rimbawan, Rimbawan; Martianto, Drajat; Dewi, Mira (Jurnal Gizi dan Pangan, 2014)
The objective of this study was to evaluate the effect of addition of phytosterol on palm oil among metabolic syndrome (MetS) subject. This study was a clinical trial with randomized double blind controlled design. Thirty adult subject (age 40—60) with MetS are divided into 2 groups. Intervention group were given palm oil enriched with 6.5% phytosterol and used as cooking oil for habitual use for 8 week. The control group were given palm oil without phytosterol. Nutrition intake was assesed by recalls every 2 weeks. Blood lipid profile, blood glucose and anthropometry were analyzed at pre and post intevention. After 8 week intervention, estimated total palm cooking oil and phytosterol consumption on intervention group were 46±23 g/day and 2±1 g/day. There were no significant change of the LDL-choleseterol level (p>0.05) but there were a significant reductiton of serum total cholesterol and triglyceride level compared the control group (respectively p=0.007 and p=0.027). In conclusion with high level palm cooking oil intake, estimated phytosterol intake had reached the target and there are slight improvement of the lipid profile on MetS subject.